Understanding the Wolbachia-mediated inhibition of arboviruses in mosquitoes: progress and challenges - Rainey, Stephanie M; Shah, Pranav; Kohl, Alain; Dietrich, Isabelle (Journal of general virology, 2014)
Arthropod-borne viruses (arboviruses) pose a considerable threat to human and animal health, yet effective control measures have proven difficult to implement, and novel means of controlling their replication in arthropod vectors, such as mosquitoes, are urgently required. One of the most exciting approaches to emerge from research on arthropods is the use of the endosymbiotic intracellular bacterium Wolbachia to control arbovirus transmission from mosquito to vertebrate. These α-proteobacteria propagate through insects, in part through modulation of host reproduction, thus ensuring spread through species and maintenance in nature. Since it was discovered that Wolbachia endosymbiosis inhibits insect virus replication in Drosophila species, these bacteria have also been shown to inhibit arbovirus replication and spread in mosquitoes. Importantly, it is not clear how these antiviral effects are mediated. This review will summarize recent work and discuss determinants of antiviral effectiveness that may differ between individual Wolbachia/vector/arbovirus interactions. We will also discuss the application of this approach to field settings and the associated risks.